Serum Neuroglobin as a Potential Prognostic Biomarker for Cognitive Impairment After Intracerebral Hemorrhage - Gao, Yu; Wang, Bo; Miao, Ye; Han, Yu (Frontiers in Neurology, 2022)
Objective Stroke is closely related to dementia, but there are few prospective studies on cognitive decline after stroke in patients with cerebral hemorrhage. Neuroglobin is an oxygen-binding protein mainly expressed in brain neurons. The aim of our current study was to determine whether neuroglobin could serve as a biomarker for cognitive prognosis in patients with intracerebral hemorrhage (ICH). Methods Three hundred and sixteen patients with ICH were consecutively enrolled in a prospective study. Baseline data such as age and gender of ICH patients on admission were recorded. Serum neuroglobin concentrations were determined by enzyme-linked immunosorbent assay (ELISA). All ICH patients 3 months after onset were divided into post-stroke cognitive impairment group (PSCI) and non-PSCI group according to MoCA assessment results. Results The PSCI and Non-PSCI groups had serum neuroglobin concentrations of (4.7 ± 0.9) and (7.5 ± 1.1) ng/ml, respectively, with a statistically significant difference between the two groups (p < 0.05). Age, gender, LDL, FBG, SBP, DBP, NHISS, and Hematoma volume were found to be adversely connected with MoCA (p < 0.05), while education, HDL, and serum neuroglobin were found to be positively correlated with MoCA (p < 0.05). After controlling for baseline data, regression analysis revealed that serum neuroglobin was remained an efficient biomarker for predicting cognitive performance in individuals with ICH (p < 0.05). The diagnostic accuracy of blood neuroglobin concentration for PSCI in ICH patients was 72.6%, the sensitivity was 67.4%, and the specificity was 75.5%, according to receiver operating characteristic (ROC) curve analysis. Conclusions Serum neuroglobin may serve as a potential biomarker to predict cognitive decline after ICH.